ФОРМИРОВАНИЕ СИСТЕМЫ ЛЕКСИЧЕСКОЙ КОМПЕТЕНТНОСТИ СТУДЕНТОВ НЕЯЗЫКОВЫХ ФАКУЛЬТЕТОВ - Каипбергенова, Ф.Т. (SCIENCE and SOCIETY, 2024)
The article discusses the importance of intercultural communication. Intercultural communication is the process of verbal and non-verbal communication between people speaking different languages and carrying different cultures, since intercultural communication, which ensures mutual understanding between people, requires people to master communicative activities in a foreign language, sufficient basic knowledge, sociocultural background, in the context which the target language exists.
Keywords: intercultural communication; sociocultural competence; sociocultural background; lexical and phraseological fund